Optimising pacemaker therapy and medical therapy in pacemaker patients for heart failure: protocol for the OPT-PACE randomised controlled trial. Issue 7 (17th July 2019) - Paton, Maria F; Gierula, John; Jamil, Haqeel A; Lowry, Judith E; Byrom, Rowena; Gillott, Richard G; Chumun, Hemant; Cubbon, Richard M; Cairns, David A; Stocken, Deborah D; Kearney, Mark T; Witte, Klaus K
Abstract : Introduction: Permanent artificial pacemaker implantation is a safe and effective treatment for bradycardia and is associated with extended longevity and improved quality of life. However, the most common long-term complication of standard pacemaker therapy is pacemaker-associated heart failure. Pacemaker follow-up is potentially an opportunity to screen for heart failure to assess and optimise patient devices and medical therapy. Methods and analysis: The study is a multicentre, phase-3 randomised trial. The 1200 participants will be people who have a permanent pacemaker for bradycardia for at least 12 months, randomly assigned to undergo a transthoracic echocardiogram with their pacemaker check, thereby tailoring their management directed by left ventricular function or the pacemaker check alone, continuing with routine follow-up. The primary outcome measure is time to all-cause mortality or heart failure hospitalisation. Secondary outcomes include external validation of our risk stratification model to predict onset of heart failure and quality of life assessment. Ethics and Dissemination: The trial design and protocol have received national ethical approval (12/YH/0487). The results of this randomised trial will be published in international peer-reviewed journals, communicated to healthcare professionals and patient involvement groups and highlighted using social media campaigns. Trial registration number: NCT01819662 .